Effects of Lung Ultrasonography-Guided Management on Cumulative Fluid Balance and Other Clinical Outcomes: A Systematic Review - Micah L.A. Heldeweg (2022)
Lung ultrasonography is accurate in detecting pulmonary edema and overcomes most limitations of traditional diagnostic modalities. Whether use of lung ultrasonography-guided management has an effect on cumulative fluid balances and other clinical outcomes remains unclear. In this systematic review, we included 12 studies using ultrasonography guided-management with a total of 2290 patients. Four in-patient studies found a reduced cumulative fluid balance (ranging from –0.3 L to –2.4 L), whereas three out-patient studies found reduction in dialysis dry weight (ranging from –2.6 kg to –0.2 kg) compared with conventionally managed patients. None of the studies found adverse effects related to hypoperfusion. The use of lung ultrasonography-guided management was not associated with other clinical outcomes. This systematic review shows that lung ultrasonography-guided management, exclusively or in concert with other diagnostic modalities, is associated with a reduced cumulative fluid balance. Studies thus far have not shown a consistent effect on clinical outcomes.